Musical segmentation - Baack, Daniel W. (SAGE knowledge. Cases., 2016)
This case study asks readers to consider the intersection of international marketing practices with music in various cultural contexts. Different musical forms are associated with different market segments, allowing for a multitude of different international marketing opportunities.